ALTERNANCE IN THE FORMATION OF COUNTRYSIDE EDUCATORS: LOOKING FOR MARKERS IN THE ACADEMIC PRODUCTIONS AND SOCIAL REPRESENTATIONS OF EDUCATION STUDENTS - Josiane das Graças Carvalho; Lourdes Helena da Silva (Universidade Federal de Sergipe, 2018)
The Education in the Countryside is part of a national movement that, starred by collective individuals of the countryside, has conquered several social, political and academic accomplishments. Among them, the Program of Support to Higher Education in Countryside Teaching - PROCAMPO, which has its origins in the fights and claims of social movements, allowed the creation of 42 new courses of Education in Rural Teaching in different Brazilian Higher Education Institutions. These courses work under Alternance training, between Time-School and Time-Community, contributing to the expansion, in our society, of the Formation by Alternance in the Higher Education, particularly in the Rural Education Graduation Courses, constituting a very recent phenomenon in the Brazilian Universities. Aiming to find a better comprehension about this educative phenomenon, the present paper has the purpose of presenting an overview of the national academic production about the alternance in the courses of formation of countryside educators, analyzing the social representations of alternance built by Rural Education students of the Federal University of Viçosa, looking for advance makers, challenges and perspectives in this pedagogical dynamic in the Higher Educaction.